Evolving aphasia: trajectories of neurodegenerative diseases. Issue 2 (9th May 2022) - Heartshorne, Rosie; Larner, Andrew J
Abstract : Aphasia, an acquired disorder of language function, may sometimes be an early and isolated sign of neurodegenerative disease or may sometimes evolve in the course of an existing neurodegenerative disorder. We present two cases in which aphasia progressively evolved, one in the context of an existing non‐linguistic cognitive disorder, and one in which aphasia was the presenting symptom. Awareness of the trajectory of neurodegenerative disorders is required when assessing patients longitudinally in clinics devoted to the assessment of cognitive disorders.